The Prospect of Reinterment of Georgian Kings Vakhtang VI and Teimuraz II in Theirhistorical Homeland as a Factor of Improvement of Russian-Georgian Relations - A. Tokarev (Международная аналитика)
The article discusses the obstacles to the reinternment of Georgian kings, buried in Astrakhan, in the context of Russian-Georgian relations coolness.